The nature and functions of coping abilities in persons after lower extremity amputation - Byra, Stanisław (Polish Journal of Public Health, 2013)
The article contains an overview of the specialist literature to date related to the process of coping with limitations resulting from the loss of a lower limb. The amputation of a lower limb is regarded as a loss: it is accompanied by the feeling of harm, injustice, punishment by fate, but is also perceived in terms of danger or a challenge. Empirical explorations confirm theoretical assumptions, which show a clear correlation between the cognitive evaluation of amputation and the limitations connected with it and the nature of an adopted remedial action. They provide evidence for the dynamics of the coping process, which depends on numerous psychosocial and physical variables. While adapting to life, persons after amputation use both adaptation and non-adaptation strategies. The factor that largely determines their choice of strategy, the frequency of its application and the results obtained, is the time which has elapsed since the operation. A significant plane for the development of the specificity of remedial activities among this group is constituted by coping with phantom pain. The whole process of coping with difficult situations connected with the loss of a lower limb is analyzed in the context of individually experienced adaptation results. The article presents the researchers’ findings concerning the regularities in this regard. The overview contains explanations of the process, which can be found both in the traditional approach (the transactional theory of stress and coping) and the modern approach relying on the indicators of growth and benefit reported after the loss of a lower limb